Contestation and Reconstruction: Natural Capital and Post-Conflict Development in Borderland Regions. Issue 1 (1st October 2014) - Zetter, Roger; Blitz, Brad K.
Though often remote and underdeveloped, borderlands are contested territories. The incorporation of borderlands into the post-conflict state highlights many important land-related paradigms, including the conversion of natural resources for economic, political, and civic purposes. This article explores the relationship between the natural resources of borderlands and their post-conflict development, management, and sustainability. Based on case study data and secondary material drawn from Croatia and Cyprus, the paper seeks to establish how the interplay of cross-border, national, and sub-national interests in post-conflict settings may contribute to the creation of new opportunities for economic development and the reconstruction of borderlands. It considers how the exploitation of natural resources may advance the agendas for the political development and incorporation of previous sites of contestation; and equally how their incorporation may constrain policies of sustainability, potentially giving rise to new conflicts. The paper sheds light on issues such as: the conversion of borderland natural capital to political capital as post-conflict states assert sovereignty claims and consolidate territorial identity; the ways in which the non-monetary value of natural capital is reconceived as commercial use value in post-conflict reconstruction; and the involvement of non-state actors and civil society in promoting environmental agendas, often as a counterbalance to state power.